Pragmatic Amplification and Rhetorical Patterning in Arabic Political Interview Discourse - Diah Ayu Sri Nariyati; Maâ€™rifatul Munjiah (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study examines conversational implicatures and departures from Grice’s maxims in political interviews on Al Jazeera Arabic’s YouTube platform, focusing on their linguistic realization in contemporary formal spoken Arabic. Employing a qualitative pragmatic approach, the data consist of purposively selected interview excerpts that indicate maxim-related departures. The analysis began with structural-linguistic examination before categorizing instances under the maxims of quantity, quality, relevance, and manner and identifying the implicatures produced. The findings reveal the dominance of quantity and quality departures, linguistically manifested through informational expansion, categorical declaratives, evaluative intensification, and temporal projection. Rather than representing conversational breakdowns, these patterns function as rhetorically structured devices embedded in Arabic media discourse. The study contributes to Arabic pragmatic scholarship by demonstrating the need for language-sensitive application of Gricean theory and offers pedagogical implications for developing pragmatic literacy in advanced Arabic language instruction.